2020
DOI: 10.4314/ahs.v20i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Medication use among pregnant women at a secondary health institution: utilisation patterns and predictors of quantity

Abstract: Background: Despite the lack of adequate studies on the safety of drugs in pregnancy, surprisingly, available evidence shows that pregnant women still take large number of drugs. Objectives: The study aim was to determine drug utilization pattern and predictors of number of medications used by pregnant women. Methods: This was a cross-sectional survey of 369 pregnant women attending a secondary health facility. Data were collect- ed using interviewer-administered questionnaire. Descriptive and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…This difference was due to participants age classification category. Our study was consistent with the study employed in General Hospital, Abeokuta 23 which showed majority of the 369 pregnant women that participated in the study were between the ages of 20-39 with a mean age of 29.65. Because women can get pregnant and bear children from puberty when they when they start getting their menstrual period to menopause when they stop getting it.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This difference was due to participants age classification category. Our study was consistent with the study employed in General Hospital, Abeokuta 23 which showed majority of the 369 pregnant women that participated in the study were between the ages of 20-39 with a mean age of 29.65. Because women can get pregnant and bear children from puberty when they when they start getting their menstrual period to menopause when they stop getting it.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed from route of administration, 67(42.9%) of the participants were most commonly used PO followed by 33(21.2%) of the participants have taken IM and 18(11.5%) have taken IV route of administration were consistent with the survey conducted in Fiche Hospital 23 showed oral dosage form was the main dosage form used across all trimesters (75.22%) as it is the simplest and easiest way for any patient to take a medication. Injectable products were also frequently used in all trimester gestation's, commonly administered via intravenous route.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, comparing the findings of our study regarding the usage of analgesics in the first trimester, 50% of women used analgesics in the first trimester of their pregnancy. Lower analgesic use was found in a previous study conducted in Nigeria to explore the medication utilization among pregnant women at a secondary health institution that showed that 34.4% took paracetamol and 4.6% took NSAIDs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is a relative lack of high-quality randomized trials in the field of hypertension in pregnancy compared with studies in essential hypertension outside of pregnancy, and greater funding and uptake of collaborative research is still required in this field. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%